Caregiver burden, coping and social support in parents of children with cancer - Villegas Chavez, Mariela; Cassaretto Bardales, Mónica (Psicooncología, 2024)
Aim: To analyze the relationship between coping strategies, social support, characteristics of migrant parent caregivers and their children with cancer on caregiver overload of such parents. Zarit Burden Interview (Zarit et al., 1980), the COPE Inventory (Carver et al., 1989) and the MOS Social Support Questionnaire (Sherbourne y Stewart, 1991) were used. Method: Eighty-two caregivers (67 mothers and 15 fathers) residing in shelters for children with cancer and their caregivers, who migrated to the city to receive treatment, participated in this study. Results: Two regression models were performed to evaluate the impact of demographic and psychological variables on caregiver burden, the first model involves the global social support scale (R2 adjusted=.43, F=9.73, p<.001) and the second the specific scales (R2 adjusted=.45, F=8.23, p<.001). Results: There is evidence the predictive role of coping strategies such as acceptance, positive reinterpretation and growth, focus and venting of emotions; global and affective social support; and sociodemographic characteristics such as parental level of education and child age in caregiver burden. Most of these variables have an inverse relationship with caregiver burden. Conclusions: The results of the study underline the crucial importance of investigating caregiver burden in the context of vulnerability. In addition, the study highlights the importance of factors such as coping strategies and social support, which play a key role in influencing caregiver burden.